Prolonged early postoperative adduction restriction is significantly associated with shoulder stiffness 1 year after arthroscopic rotator cuff repair - Miyasaka, Yuki; Sekiguchi, Takahiro; Takahashi, Norimasa; Nagaoka, Toshiki; Kimura, Keisuke; Matsuda, Kohei; Matsuki, Keisuke; Hoshika, Shota; Sugaya, Hiroyuki; Kawashima, Itaru (JSES international, 2025)
Postoperative shoulder stiffness (POSS) is one of the most common complications of arthroscopic rotator cuff repair (ARCR). Although adduction restriction is commonly observed in the early postoperative period, it remains unclear whether a prolonged duration of this restriction impacts the development of POSS. The aim of this study was to investigate whether early postoperative adduction restriction is associated with the occurrence of POSS 1 year after ARCR. This retrospective cohort study included patients who underwent ARCR at a single institution between April 2017 and June 2018. A total of 96 shoulders were analyzed. Active and passive range of motion were assessed preoperatively and at 12 months postoperatively. Adduction restriction was evaluated in two positions: the droop position and the intermediate position. Adduction restriction was defined as resolved when the medial side of the arm made contact with the side of the body. Based on these evaluations, the duration of persistent postoperative adduction restriction was evaluated. POSS was defined as passive external rotation at the side of less than 30° at 12 months after surgery according to the previous studies. Patients were assigned to one of two groups: Group N, without POSS group, or Group S, with POSS group. Propensity score matching was used to ensure comparability between groups. The duration of persistent postoperative adduction restriction was compared between the groups. After propensity score matching, 38 shoulders were analyzed (19 in Group N and 19 in Group S). While no significant difference in the duration of persistent postoperative adduction restriction in the droop position between the groups was observed, the duration in the intermediate position was significantly shorter in Group N compared to Group S (7 ± 3 weeks vs. 10 ± 4 weeks, P = .007). The duration of persistent adduction restriction in the intermediate position was significantly longer in shoulders with POSS at 12 months after ARCR compared to those without POSS. Prolonged early postoperative adduction restriction may associate with the occurrence of POSS 12 months after ARCR.